If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + -149 + 67 = 180 Reorder the terms: -149 + 67 + 6y = 180 Combine like terms: -149 + 67 = -82 -82 + 6y = 180 Solving -82 + 6y = 180 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '82' to each side of the equation. -82 + 82 + 6y = 180 + 82 Combine like terms: -82 + 82 = 0 0 + 6y = 180 + 82 6y = 180 + 82 Combine like terms: 180 + 82 = 262 6y = 262 Divide each side by '6'. y = 43.66666667 Simplifying y = 43.66666667
| 2*2y-5y=-4 | | (x-3)-(x+2)=6x | | 1x+1y=9 | | b^3=16b | | 8x-34=32+23x | | 7w+17=10 | | 3(5-3x)-2(5+2x)=3(x+1)-6x-23 | | 40=5x+3x+8 | | 8m^3-162m=0 | | -12=3v+10 | | 16=7x+12 | | 2x-3x=6x | | (5p+1)(p+5)=0 | | y+64=11 | | -6a=2 | | 5x+43=9x+6 | | 94=6x+6x+10 | | 7(b-2a)=5(-3a+1) | | 5m+9=3(m-6)+7 | | y+60=11 | | 0.7x+0.6=-0.8 | | y+6-1=11 | | 14(x-y)=336 | | 3x-7+x=2x-9 | | 67x+8=41+21x | | 12(x+y)=336 | | 2(x+4)=x+6 | | 6u=5u-8 | | 6+3x=1x | | 5=4x+6x+5 | | 10=-6k+k | | -6=-2n |